An investigation into the ecology of the pine marten (Martes martes) in Killarney National Park - Lynch, Áine B. (Trinity College (Dublin, Ireland). Department of Zoology, 2006)
The majority of the research for this thesis was carried out on a reestablished population of pine marten in Killarney National Park (KNP). I explored the success of the translocation and used distributional, biometric and reproductive data as the criteria by which to measure that success. I also examined the diet of the pine marten in the park. Two novel methods for monitoring pine martens populations were also investigated (hair traps and the use of the SRY gene to identify sex from non-invasively collected samples) and the results of both these chapters have been published. Finally, I examined the current level of genetic diversity within the pine marten population in KNP compared to the source population from which the translocated animals were derived and to samples taken from animals located throughout the countryside. In addition I gave an evaluation of the usefulness of the genetic markers used in this study for describing different aspects of the molecular ecology of the pine marten.
Keywords: Zoology, Ph.D.; Ph.D. Trinity College Dublin